Simply Small Men?: examining Differences Between Females and Males Radicalized in the United States - Yon, Rachel (Women & criminal justice, 2019)
From Leila Khaled to women who joined the Islamic State, it seems clear that radical ideologies know no gender bounds. Despite this history of women’s involvement in terrorist movements and a growing amount of research on women and political violence, there have been few attempts to contrast radicalized females from their male counterparts, either in terms of broad demographic characteristics or more specifically according to ideological orientation. We remedy this shortcoming in two steps. First, we examine previous work to understand both how females may differ from males in terms of their recruitment and radicalization process but also how these differences may manifest across various ideologies. Second, using the Profiles of Individual Radicalization in the United States database, we compare radicalized U.S. females to radicalized U.S. males both as an aggregate group and across different ideological groupings. This work provides simple but important insights for scholars and policy makers examining the role of gender in radicalization.